2018
DOI: 10.1038/s41420-018-0075-0
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting sphingolipid metabolism as an approach for combination therapies in haematological malignancies

Abstract: Conventional chemotherapy-based drug combinations have, until recently, been the backbone of most therapeutic strategies for cancer. In a time of emerging rationale drug development, targeted therapies are beginning to be added to traditional chemotherapeutics to synergistically enhance clinical responses. Of note, the importance of pro-apoptotic ceramide in mediating the anti-cancer effects of these therapies is becoming more apparent. Furthermore, reduced cellular ceramide in favour of pro-survival sphingoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 99 publications
(166 reference statements)
1
47
0
1
Order By: Relevance
“…Ceramide is present in small amounts in cell membranes, as intermediate in the metabolism of sphingolipids or as a result of sphingomyelinase activity, which produces ceramide from SM ( Kartal Yandim et al, 2013 ; Peetla et al, 2013 ). Altered ceramide metabolism in cancer has been described as an effective drug resistance mechanism: tumors have low levels of ceramide by increasing SM synthesis or by preventing its degradation ( Senchenkov et al, 2001 ; Lewis et al, 2018 ). One possible strategy is to increase ceramide membrane levels using short chain ceramide and use lipid rafts as platforms to enhance apoptosis, since in presence of an excess of ceramide, cholesterol is displaced from lipid rafts, inducing activation of Fas/CD95 pathway ( Selzner et al, 2001 ; Stover and Kester, 2003 ; Stover et al, 2005 ; Chiantia et al, 2007 ).…”
Section: Mlt For Cancer Therapy: a Brief Outlinementioning
confidence: 99%
“…Ceramide is present in small amounts in cell membranes, as intermediate in the metabolism of sphingolipids or as a result of sphingomyelinase activity, which produces ceramide from SM ( Kartal Yandim et al, 2013 ; Peetla et al, 2013 ). Altered ceramide metabolism in cancer has been described as an effective drug resistance mechanism: tumors have low levels of ceramide by increasing SM synthesis or by preventing its degradation ( Senchenkov et al, 2001 ; Lewis et al, 2018 ). One possible strategy is to increase ceramide membrane levels using short chain ceramide and use lipid rafts as platforms to enhance apoptosis, since in presence of an excess of ceramide, cholesterol is displaced from lipid rafts, inducing activation of Fas/CD95 pathway ( Selzner et al, 2001 ; Stover and Kester, 2003 ; Stover et al, 2005 ; Chiantia et al, 2007 ).…”
Section: Mlt For Cancer Therapy: a Brief Outlinementioning
confidence: 99%
“…Since our results showed that SPHK1 plays functional roles in regulating the survival of breast CSCs and non-CSCs and given that recent studies have highlighted the potential of utilizing agents that manipulate sphingolipid metabolism to augment the chemotherapeutic efficacy in hematological malignancies [70], we sought to investigate whether inhibitors targeting SPHK1 and the sphingolipid rheostat might exert anti-proliferative effects in breast CSCs and non-CSCs.…”
Section: Apoptosis Induced By Sphk1 Depletion Is Mediated Through Stat1mentioning
confidence: 99%
“…Taken together, these data suggest that the modulation of ceramide and ceramide synthases may be a viable therapeutic target in GBM 5.4. Sphingosine 1-Phosphate-Mediated Cell Signaling S1P has roles in cell survival, migration and angiogenesis, and is known to play an important role in cancer [194][195][196][197][198].…”
Section: Ceramide Synthasementioning
confidence: 99%